Analysis of Tourism Destination Loyalty of Ragunan Zoo in Jakarta - SUPRIYAD, Edy (Journal of Environmental Management and Tourism, 2018)
The most popular tourist destination visited in Jakarta is Ragunan Zoo. Ragunan Zoo is a 147-hectare park and inhabited more than 2.009 animals and overgrown more than 20,000 trees to make the atmosphere cool and comfortable environment. The area was arranged and woke up and partly still developed into a modern Ragunan Zoo as the identity of the city of Jakarta, located in Ragunan, South Jakarta. The purpose of this research includes (1) To test among variables tourism destination parts, service quality has affect to destination loyalty (2) To test among variables tourism destination parts, service quality have affect to Satisfaction (3) To test the effect between variable satisfaction to the destination loyalty. The population in this study covers all tourist visited Ragunan Zoo. The sample in this study was taken using non-probability sampling method, with purposive sampling technique. The number of samples is 150 samples from tourists who have visited Ragunan Zoo. Dependent variable is destination loyalty and independent variable consists of tourism destination parts, service quality and intermediary variable is satisfaction. Analysis of data using Structural Equation Modeling with PLS software (Partial Least Square) The results obtained are (1) Tourism Destination Parts, Service Quality has significant effect to Tourist Destination Parts, while Service Quality has significant effect to Destination Loyalty (3) Tourist Satisfaction has no significant effect to Destination Loyalty at Ragunan Zoo.